Fabrication And Properties Of Transparent, Conductive And Flexible Multi-Walled Carbon Nanotubes (Mwcnts)/Epoxy Composite Film - Saw, Lian Na (2012)
Optically transparent, conductive, and mechanically flexible epoxy thin films nanocomposite are produced in the present study. Investigations on the properties of different epoxy/hardener ratios, two different aspect ratios of multiwalled carbon nanotubes (MWCNTs) and MWCNTs loading in epoxy were carried out. The tensile test and dynamic mechanical analysis (DMA) results show that the properties of the epoxy system are governed by different resin/hardener ratios. It was shown that the specimens with an epoxy-to-hardener ratio of 100: 45 (Systems A) exhibit higher tensile strength, Young’s modulus and storage modulus compared to an epoxy-to-hardener ratio of 100: 60 (System B). Two types of MWCNTs with different aspect ratios and loadings were dispersed in epoxy resin through an ultrasonication process and compression molded to form the epoxy thin films nanocomposite. Results showed that nanocomposites containing MWCNTs with a lower aspect ratio (S-MWCNTs) exhibit enhanced electrical conductivity compared to those with a higher aspect ratio (L-MWCNTs). Higher Young’s modulus, tensile strength and thermal stability were observed in S-MWCNTs thin film nanocomposite if compared to those of L-MWCNTs. This behavior was associated with the better S-MWCNTs dispersion in the epoxy resin. A sheet resistance as low as 100 Ω/sq with nearly 60 % optical transparency in 550 nm is achieved with the addition of MWCNTs in epoxy.